Changes in the calcium metabolism of Biomphalaria glabrata experimentally infected with Angiostrongylus cantonensis. Issue 2 (June 2014) - Tunholi-Alves, V.M.; Tunholi, V.M.; Garcia, J. Silva; Costa-Neto, S.F.; Maldonado, A.; Santos, M.A.J.; Thiengo, S.C.; Pinheiro, J.
Abstract Levels of calcium in the haemolymph and reserves in the shell of Biomphalaria glabrata experimentally infected by Angiostrongylus cantonensis were determined for the first time. At the same time, histochemical analyses of the digestive gland of infected and uninfected snails were performed to better understand the possible changes in metabolism of calcium in these organisms. After 1, 2 and 3 weeks of infection, the snails were dissected for collection of haemolymph and separation of tissues. The highest calcium concentrations in the haemolymph were found 2 weeks after infection, with a 39.61% increase in relation to the respective control group. However, there was a significant reduction in the concentration of this ion in the haemolymph of infected snails after 1 week of infection in relation to the uninfected specimens. In parallel, intense hypocalcification was shown in the shell of infected snails 1 and 2 weeks after infection, differing significantly in relation to the respective control groups. Morphological changes in the digestive gland of infected snails were also observed, confirming the role of this ion as an important element in the parasite encapsulation process.